The Landscape of Risk Management, Insurance, and Social Protection in Nepal - Editorial Team (Nepalese Journal of Insurance and Social Security, 2025)
Nepal’s systems for insurance, risk management, and social protection remain fragmented and poorly coordinated. Multiple institutions work independently, with little collaboration or strategic alignment. As a result, efforts to protect people’s lives, property, and livelihoods are often inefficient and scattered. Risk management in Nepal is generally divided into two areas: disaster risk and enterprise risk. Disaster risk is handled mainly by the National Disaster Risk Reduction and Management Authority (NDRRMA), focusing on natural hazards. Enterprise and personal risks fall under commercial insurance companies regulated by the Nepal Insurance Authority (NIA). However, commercial insurance faces many issues, such as slow growth, low public awareness, underinsurance, mis-selling, and adverse selection. Social protection programs also operate in isolation. The Health Insurance Board (HIB) runs a social health insurance program for low- and middle-income groups. The Social Security Fund (SSF) offers formal sector workers protection against illness, maternity, loss of income, and retirement insecurity. Other institutions, such as the Employees Provident Fund (EPF), Deposit and Credit Guarantee Fund (DCGF), and some community and microinsurance schemes, cover specific areas. Despite these efforts, a large portion of the population remains unprotected. Duplication of work, weak coordination, and overlapping responsibilities hinder progress. A major gap is the lack of academic, or research institutions dedicated to insurance, risk, and social protection. There is also a serious shortage of skilled professionals. Nepal’s education sector has not adequately responded to the growing need for research, training, and professional development in these fields. Institutions that can train experts and connect policy, market needs, and academic knowledge are urgently needed. Against this backdrop, NJISS aims to serve not only as an academic journal but also as a platform for knowledge sharing and policy engagement. We hope to contribute to public understanding, academic discussion, and informed decision-making through the publication of high-quality research. Inside the 8th Issue This 8th issue of NJISS features ten research articles. Four of them explore how behavioral, social, and psychological factors affect the adoption of insurance in Nepal. These studies examine consumer attitudes, agent influence, and decision-making in both rural and urban settings for life and livestock insurance. Two papers analyze the financial and operational efficiency of Nepalese non-life insurance companies. They assess profitability, investment strategies, and performance, offering useful insights for improving sector competitiveness. The remaining four articles focus on broader economic themes under the title “Financial Inclusion, Economic Policy, and Capital Market Dynamics.” These papers examine the effects of monetary policy, banking competition, corporate social responsibility (CSR), and foreign investment on financial inclusion and economic growth. We thank all contributing authors for their quality research and extend our gratitude to the peer reviewers for their valuable feedback. We are also thankful to our readers and subscribers, whose support motivates us to continue improving. NJISS now moves to a biannual publication schedule. The 8th issue covers January to June, and the 9th issue (July–December) will be published in an online-first format. We invite researchers to submit manuscripts year-round that align with the journal’s key focus areas.